2015
DOI: 10.1088/1748-9326/10/5/054018
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing intensity of monsoon low-frequency intraseasonal variability over India

Abstract: Understanding the changing nature of the intraseasonal oscillatory (ISO) modes of Indian summer monsoon manifested by active and break phase, and their association with extreme rainfall events are necessary for probabilistic estimation of flood-related risks in a warming climate. Here, using groundbased observed rainfall, we define an index to measure the strength of monsoon ISOs and show that the relative strength of the northward-propagating low-frequency ISO (20-60 days) modes have had a significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 35 publications
4
49
1
Order By: Relevance
“…In the Indian monsoon region, the growth of vegetation is mainly controlled by precipitation [6,7], which has experienced significant changes in intensity and frequency over the past half-century [8][9][10]; these changes will certainly cause shifts in vegetation phenology, such as a significant advance in the start of growing season (SOS) in northern parts (e.g., Punjab, Haryana) of India [11]. Therefore, accurate depictions of vegetation phenology in the Indian monsoon region are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian monsoon region, the growth of vegetation is mainly controlled by precipitation [6,7], which has experienced significant changes in intensity and frequency over the past half-century [8][9][10]; these changes will certainly cause shifts in vegetation phenology, such as a significant advance in the start of growing season (SOS) in northern parts (e.g., Punjab, Haryana) of India [11]. Therefore, accurate depictions of vegetation phenology in the Indian monsoon region are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, demise dates are strongly associated with the HF‐ISO phases across entire India and demise of the ISM occurs mostly in phase 7 of HF‐ISO except some grid points over northeast India (Figure h). Onset of monsoon rainfall occurring in unfavorable phases of LF‐ISO over the eastern India coincide with the fact that most of the low‐pressure systems that develop over the BoB, in unfavorable LF‐ISO phases in many cases, propagate toward this region and cause substantial amount of rainfall during May–early June (Goswami et al, ; Karmakar et al, , ). This may mark the onset of the ISM rainfall over these regions just before the low‐level westerlies strongly establishes over the domain.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we do not consider data over these regions in any of our analysis. Many earlier studies also neglected these regions to study monsoon variability (Karmakar et al, 2015;Krishnamurthy & Shukla, 2007). We also use National Centers for Environmental Prediction/National Center for Atmospheric Research Reanalysis-1 (Kalnay et al, 1996) data sets to understand large-scale atmospheric patterns during onset/demise of the ISM.…”
Section: Data Set and Methodologymentioning
confidence: 99%
“…The reduction in seasonal mean rainfall over India in recent decades (Naidu et al ., ) is also associated with an increase in localized heavy precipitation events (Karmakar et al ., ). It was also found that the amplitude of intraseasonal variability in rainfall during summer is weakening over India (Karmakar et al ., ). In contrast to the literature that suggests a weakening of ISMR in recent decades, a few studies conclude that, in spite of global warming, there is no clear evidence that the strength or variability of ISMR has exhibited any long‐term trend (Kripalani et al ., ; Goswami et al ., ; Kumar et al ., ; Guhathakurta and Revadekar, ).…”
Section: Introductionmentioning
confidence: 99%